10 Jenis Kecenderungan Perilaku Menyimpang Siswa SMA Negeri di Kota Bandung - Hamzah, Rifqy Muhammad; Yusuf, Syamsu; Budiamin, Amin; Nurhudaya, Nurhudaya; Sudrajat, Dadang (Jurnal Bimbingan dan Konseling Terapan, 2021)
ABSTRACTThe purpose of this study was to determine the general description and types of deviant behavior in schools carried out by state high school students in the city of Bandung. The study used a descriptive method with a quantitative approach. The research sample consisted of 1,793 students belonging to 14 schools in 8 areas in the city of Bandung. The results showed that more students answered disagree on the statement of deviant behavior. While the tendency of deviant behavior that is often carried out by students is people who sleep (sleepers), scouts, dissatisfied people (not satisfied), animals (behave like animals), angels (feel good), skeptics, pests (disturbing), procrastinators (work procrastinators), hyperactivity (very active), and name-callers.Keywords: misbehavior, students, teachers, schools ABSTRAKTujuan penelitian ini adalah untuk mengetahui gambaran umum dan jenis kecenderungan perilaku menyimpang di sekolah yang dilakukan oleh siswa SMA Negeri di Kota Bandung. Penelitian menggunakan metode deskriptif dengan pendekatan kuantitatif. Sampel penelitian terdiri dari 1.793 siswa yang termasuk ke dalam 14 sekolah pada 8 wilayah di Kota Bandung. Hasil penelitian menunjukkan bahwa lebih banyak siswa menjawab tidak setuju pada pernyataan kecenderungan perilaku menyimpang. Sedangkan kecenderungan perilaku menyimpang yang sering dilakukan oleh siswa adalah the sleeper (tukang tidur), the snoop (pengintai), the malcontent (tidak puas), the animal (berperilaku seperti binatang), the angel (merasa baik hati), the skeptic (skeptis), the pest (pengganggu), the procrastinator (penunda pekerjaan), the hyperactive (sangat aktif), dan the name caller (pemanggil nama).Kata Kunci: perilaku menyimpang, siswa, guru, sekolah